An analysis of Internet Banking in Portugal: the antecedents of mobile banking adoption - Couto, João Pedro Almeida (2014)
This is an open access journal distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.